2015
DOI: 10.1016/j.ijporl.2015.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pepsin in tears of children with laryngopharyngeal reflux disease

Abstract: 20% of the children with diagnosed LPR showed pepsin in the tears. Our specific investigation might provide information regarding sinusitis or dacryostenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
1
36
0
2
Order By: Relevance
“…Our finding is that pepsin is present in control, asymptomatic subjects and at measurable levels and does not have discriminatory potential for separating GERD from controls. This finding is consistent with other reports which found no difference between cases and controls, or found controls had higher levels . A recently published study concluded a value for Peptest in predicting GERD; however, there was no difference between controls and GERD patients when all sampling was taking into account, suggesting low reproducibility .…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is that pepsin is present in control, asymptomatic subjects and at measurable levels and does not have discriminatory potential for separating GERD from controls. This finding is consistent with other reports which found no difference between cases and controls, or found controls had higher levels . A recently published study concluded a value for Peptest in predicting GERD; however, there was no difference between controls and GERD patients when all sampling was taking into account, suggesting low reproducibility .…”
Section: Discussionsupporting
confidence: 92%
“…The LPR is involved in the development of many otolaryngological diseases through the deposit of gastroduodenal enzymes into the mucosa of the upper aerodigestive tract. Thus, pepsin has been identified in the laryngeal [5], hypopharyngeal [6], oral [7], nasal [7], tears [8], and Eustachian mucosa as well as in the secretion of chronic rhinosinusites [9] and chronic media otitis [10]. The involvement of reflux in the development of dental disorders has been suspected for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for demonstrating reflux events are multi-channel intraluminal impedance (MCII) and pH monitoring studies [21,22,23]. Unfortunately, these tests are expensive, not easily applicable, and are often either not accepted or tolerated by patients [23,24,25]. Therefore, in clinical practice, a diagnosis based on endoscopic findings and clinical questionnaires is usually preferred [9,11,20,23,24,25].…”
Section: Introductionmentioning
confidence: 99%